Analysis of Control Characteristics of Electromagnetic and Permanent Magnet Hybrid Suspension System - 程虎; 张晓; 李云钢; 杜发喜 (机车电传动)
This paper studied the suspension force calculation method and established the mathematical model of permanent magnet hybrid electromagnetic suspension system. The effects of permanent magnet on the model parameters and control system had also been analyzed from suspension force, electric characteristics and control quality separately. The results which can guide the design and parameter selection of cascade controller. The stable control of single magnetic hybrid suspension system has been achieved.